Kinetic Parameters Determination of Benzene Vapor Adsorption on Activated Carbon Using Differential Permeation Technique - Mindaryani, Aswati; Tyoso, Boma W; Sediawan, Wahyudi B; Supranto, Supranto (ASEAN Journal of Chemical Engineering, 2005)
Equilibrium and kinetic data are very important for a reliable design of a large-scale adsorption system. The objective of the research was to determine the particle scale kinetic parameters of strongly adsorbed volatile organic compounds (VOCS)in activated carbon (AC) by using the differential permeation technique. The experimental rig consisted basically of upstream and downstream reservoirs separated by a slab-shaped AC that is 2 mm thick. After cleaning the slab overnight at 400 K and under vacuum condition, the experiment was started by opening the valve to allow vapor to diffuse through the AC. The upstream and downstream pressures were continuously recorded until equilibrium was reached. Another experiment was run by increasing incrementally the upstream pressure. The same experiment was carried out using nonadsorbed gas (argon) to estimate both Knudsen permeability and viscous permeability. The Knudsen, viscous, and surface diffusivities were determined by matching the total permeability against the experimental data. From the data obtained, it was found that both porosity and surface diffusivity change with loading. The surface diffusivity of benzene vapor in AC pores does not follow the Darken model, but it follows the hydrodynamic model of Gilliland, especially when the porosity is relatively constant at high loading. Keywords: Adsorption, benzene, differential permeation, kinetic, and volatile organic compounds (VOCs).